ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONVERSI LAHAN PANGAN PADI MENJADI LAHAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN LABUHAN BATU - Aprina Tanjung; Zuhrina M. Nawawi; Muhammad Arif (Studia Economica : Jurnal Ekonomi Islam, 2021)
The purpose of this study is to find out how the conversion of rice food land into oil palm plantations is related and related to food security, what factors make farmers so that farmers convert rice food land into oil palm plantations and to determine the effect of income, production costs and social factors on rice field conversion in Labuhanbatu Regency. This study uses a quantitative approach and uses primary data by distributing questionnaires to rice farmers who convert land into oil palm plantations in Labuhanbatu Regency. The population in this study was 100 Paddy Rice Farmers who converted land into oil palm plantations in Labuhanbatu Regency with the sampling technique using the Slovin formula with Likert Scale measurements. The data is processed through the SPSS Version 22.0 program with the technique of multiple linear regression analysis. The results showed that land area, production costs and income had a positive and significant effect on land conversion in Labuhanbatu Regency. From the results of the t test proves that partially the variables of land area, production costs and income have an effect on land conversion. Then from the results of the f-count value is greater than the f-table, namely (20.849 > 2.47) with a significant value of 0.000 < 0.05